THE GROWTH OF DEVELOPMENT OF ARTIFICIAL AND NATURAL COTTON SCREENS IN THE SAND (Modern American Journal of Biological and Environmental Sciences, 2026)
Nitrogen migration depends on fertilizer rates and precipitation and increases in soils with a lighter texture. Based on research conducted on light loamy soil, N-NO3 is rapidly washed out of the 0-15 cm layer and accumulates only slightly in the 15-30 cm layer.